Eve of the Emperor Penguin (Magic tree house, 40,, 2009)
The magic tree house takes Jack and Annie to Antarctica to search for the fourth secret of happiness for Merlin.

Blizzard of the blue moon (Magic tree house, 36,, 2006)
The magic tree house carries Jack and Annie to New York City in 1938 on a mission to rescue the last unicorn.

Leprechaun in late winter (Magic tree house series.Merlin missions, 15,, 2012)
Jack and Annie travel back to nineteenth-century Ireland to inspire a young Augusta Gregory to share her love of Irish legends and folktales with the world.

Carnival at candlelight (Magic tree house, 33,, 2006)
While on a mission to prove to Merlin that they can use magic wisely, Jack and Annie travel to seventeenth-century Venice, Italy, to save the city from disaster. Merlin has asked Jack and Annie to help on another Merlin Mission. This time they head back into history to Venice, Italy, in the 1700s. With the help of some new friends, a research book, and a mysterious rhyme from Merlin, the heroes will save the beautiful city from a flood! Yet another Magic Tree House book that will engage kids with history, magic, and nonstop action from beginning to end. Merlin has a new mission for Jack and Annie: save the Grand Lady of the Lagoon from a terrible disaster! To find her, they must travel back over 250 years ago to Venice, Italy, on the night of the annual Carnival celebration. But Merlin's directions are very confusing! As Jack and Annie wander among the costumed crowd, no one is who they seem to be, the clocks all tell different times, and water is mysteriously rising in the streets. Seeking help from Venice's ruler, they find themselves thrown into a dark dungeon filled with rats. How will Jack and Annie save themselves and the Grand Lady, too? There can only be one solution-magic! Mary Pope Osborne is a master of bringing faraway places to life. In Carnival at Candlelight she sends young readers to one of the most glorious cities in the world for an adventure filled with history, mystery, and magic.
Book of magic , Carnival , Grand lady of the lagoon , Rats! , Lorenzo , Disaster , King and the ruler , Home by day , Painting , More facts about Venice.

Abe Lincoln at last! (Magic tree house, 47,, 2013)
The magic tree house whisks Jack and Annie to Washington D.C. in the 1860s where they meet Abraham Lincoln and collect a feather that will help break a magic spell.